Distance Learning Activities For The Nahwu Subjects For Students In Islamic Boarding School - Maturedy, Faris (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2024)
This research is to provide a detailed description of the remote muraja'ah program that has been executed by a teacher at Al Mawarits An Nabawiyyah Islamic Boarding School. This program seeks to provide students with an alternative approach to reviewing their lessons encountered during their tenure at the Islamic boarding school. The present study employs a qualitative methodology. Observation and interviews were used as the methods of data collection. Once the data is gathered and considered adequate, it undergoes three critical steps of analysis: reduction, presentation, and drawing conclusions. The research findings suggest that this program comprises three distinct phases: design, execution, and reflection. The program design include socialization activities targeting the guardians of the students. Subsequently, the teacher compiles the resources on Nahwu and Sharaf utilizing the Blooket platform consulting with specialists. Implemented over the Maulid holiday, this program offers students three assignments and has garnered a favorable reception from their guardians. Upon reflection of this program, the instructor has come to the realization of their constraints in effectively using the digital learning platform. Therefore, I was driven to attempt under the supervision of a specialist. Consequently, the teacher astutely refrained from broadening the range of additional instructional resources. The pertinent factor to consider is the proportion of students who dedicate their time to assisting their parents instead of engaging in phone usage. Augmenting the range of the content may raise apprehensions that the students may become more engrossed in using their mobile devices while pretending to engage in studying.